THE INFLUENCE OF SELF ESTEEM AND FAMILY SUPPORT ON RESILIENCE IN CULINARY SECTOR SMEs MEDAN DISTRICT, JOHOR - Abdul Halim Saragih; Patisina; Suryani Hardjo (RADJA PUBLIKA, 2023)
This study aims to determine the effect of self-esteem and family support on resilience in MSME actors in the culinary sector in Medan Johor District. The population of this study were 54 MSME actors in the culinary sector in the Medan Johor sub-district. Sampling of this study by total sampling technique, where the entire population is a sample of 54 people. This research uses quantitative methods. Measuring tools used are self-esteem scale, family support scale and resilience scale. Data analysis using multiple linear regression test. The results of this study indicate that (1) There is an influence of Self Esteem on the resilience of MSME entrepreneurs in the Medan Johor sub-district, where the significance value is 0.000, namely 0.05, so the hypothesis is rejected. Based on this research, data was obtained that MSME entrepreneurs with high family support had high resilience, with a contribution of 5.45%. (3) There is an influence of self-esteem and family support on the resilience of MSME entrepreneurs in Medan Johor District, with a significance of 0.000, i.e. <0.05, so the hypothesis is accepted. This means that the self-esteem variable and the family support variable have a significant influence on the resilience of MSME entrepreneurs by 68.8%. Other results obtained from this study are that resilience and family support are in the high category while self-esteem is in the low category.